Evanescent field study on a U-shaped silica fiber absorption sensor using non-sequential ray tracing - Rashid A.R.A.; Mokhtar W.M.; Dasuki K.A.; Ehsan A.A.; Shaari S. (Trans Tech Publications Ltd, 2024)
Indexed by SCOPUS